Avaliação da indiferenciação celular e indução de neurodiferenciação em co-cultivo de fibroblastos NIH 3T3 com células mononucleares do sangue de cordão umbilical - Marinowic, Daniel Rodrigo (2012)
Cellular therapy represent a new frontier for the treatment of several diseases, including diseases related to central nervous system. Human umbilical cord blood is an attractive source of stem cells; however, it has a heterogeneous population with a small amount of mesenchymal stem cells. Currently, cell reprogramming induced by different methodologies can confer pluripotency to differentiated adult cells. The objective of the study was to evaluate the reprogramming potential of fibroblasts and neural differentiation after co-culture with umbilical cord blood mononuclear cells. This study was approved by the Ethics Committee of PUCRS (CEP 11/05504). Cells were obtained from four human umbilical cord blood. Cell suspensions were fractionated at gradient of density 1077. The mononuclear cells of each sample were cultured for 7 days and later, the culture was infected with 105 cells of mouse fibroblast cell line NIH 3T3 and co-cultured for 6 days. To evaluate the pluripotency it was performed RNA extraction and later, amplification using primers specific for pluripotency genes. The differentiation was also confirmed by the adipogenic and osteogenic differentiation. Neural differentiation of the reprogrammed cells was obtained by the method described by Song et. al (2008) and evaluated by immunofluorescence. Population growth was quantified by hemocytometer. All co-cultured cells showed adipogenic and osteogenic differentiation capacity. After co-cultivation cells began transcribing the pluripotency gene KLF4. Statistically significant differences in the parameters area, diameter, optical density and fractal dimension were observed by confocal microscopy in reprogrammed and neural differentiated cells. The population of reprogrammed cells doubled every three days until the addition of the last medium of neural differentiation, when cultures became quiescent until the end of the neural differentiation. The contact in form of co-cultivation of fibroblasts with umbilical cord blood mononuclear fraction for six days promoted the reprogramming of these cells to a indifferentiation stage, allowing the induction of neural differentiation later.